ESENSI SERTA EKSISTENSI BARONG DAN RANGDA: Eksplorasi Teologi Hindu - I Made Ari Susandi (Pangkaja: Jurnal Agama Hindu, 2021)
The dynamics of Balinese life are constantly under the spotlight because of the variety of cultural activities that blend with various aspects of life. The arts of barong and rangda are spread across all districts and cities in Bali, but not all pakraman villages or temples have barong and rangda arts. This is due to the existence of barong and rangda in the religious dynamics of Balinese Hindu society. although in reality barong and rangda are not merely a form of art, but furthermore they are the implementation of theology (divine teachings) of Hinduism, both regarding the philosophical side (the essence) of religion and psychology (psychological/emotional aspects) of religion. This article is the result of qualitative research by applying the theological description approach and philosophy of art. The existence of Barong-Rangda is very important in the socio-religious life of Balinese people, because people still need symbols to express their devotion to God/Ida Sang Hyang Widhi Wasa.